Malnourished children: A study of parents' status - Helmi Lubis; Jaminsen Sinaga; Mansur Karo-karo; Rahayu Saat; Sjarikat Tarigan (Paediatrica Indonesiana, 1985)
A retrospective study had been done on the parents of hospitalized malnourished children from January 1981 until December 1982 at the Department of Child Health Dr. Pirngadi Hm;pital, Medan, Indonesia, as to their occupation, educational level, family size and the subsequential number of the affected child in the families. Diagnosis of malnutrition was based on the inadequate body weight according to age. There were 759 malnourished children, with peak incidence in the age group of 1-5 years (49.94%) followed by the age group of 0-1 years (37.94%). The affected child was mostly the first child (21. 62%) in a family with 2 children. Most of the parents (50.32%) have no regular job. The educational level of the fathers and mothers were mostly elementary school, respectively 32.8% and 50.46%. In conclusion, most of the parents had low education and unstable income.